Are structured products fairly priced?: Barrier reverse convertibles and turbo warrants in the Swiss market - Barbosa, Joana Margarida de Sousa (2020)
The investments in structured products have been increasing in the past few years and, jointly, also the complexity of such products has substantially intensified. In accordance, this thesis was developed with the objective to present the current status of the structured products market, namely in Switzerland, as it is the one of the most developed markets in Europe. Hence, it was analysed a sample of Barrier Reverse Convertibles and Turbo Warrants issued by the biggest Swiss financial institutions, which will permit a clear overview of the price fairness of these financial derivatives and, consequently, support more accurate and informed investment decisions. In fact, this thesis was based on previous studies which revealed that the vast majority of this type of products is substantially overpriced. Thus, besides than presenting a practical overview of this reality, other main objective was to understand the reasons and motivations of investors that could justify the increasing demand for such products. Based on the theoretical price obtained using the Black & Scholes (1973) and Merton (1973) model, and comparing that value with the market price, it was possible to conclude that, in general, all products presented an overprice considered economically relevant, being Barrier Reverse Convertibles typically more overpriced than Turbo Warrants. Regarding the main issuers of each type of product, Bank Vontobel was the financial institution with most fairly priced products related to Turbo Warrants, while Bank Julius Baer should be the safest choice for investments in Barrier Reverse Convertibles.